Strategi Negosiasi Dalam Menyelesaikan Konflik Organisasi - Fauzi, Nurul Baridah; Sumarni , Lilik; Esfandiary , Shifana; Al Balqis , Kaiza Nazwita; Aprihatno, Arif (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
This research explores the factors that cause conflict in the MRadio UMJ organization and the steps taken to overcome them. Through interviews and searches with various sources, it was found that conflicts were caused by a lack of effective communication, differences in goals between members, a less participatory leadership style, an imbalance in the division of tasks, and dissatisfaction regarding member welfare. To address these conflicts, a collaborative and strategic approach was adopted that involved identifying the source of conflict, gathering information, facilitating open dialogue, identifying common interests, finding mutually beneficial solutions, and implementing and evaluating solutions. The head of the organization plays an important role in providing guidance and making final decisions where necessary. This approach aims to strengthen cooperation and cohesion within the organization and ensure fair and efficient problem-solving. The results of this study are expected to provide insights and practical guidance for other organizations facing similar conflicts. Keywords: Communication, Division of Duties, Leadership, Member Welfare, Negotiation